Dialectal Variations Of Adjectives In Kaili Ledo And Kaili Ado: A Contrastive Study - Arul Arul; Alya Alya; Andi Isma Wardani; Mohammad Amil Barokah (Applied Linguistics: Innovative Approaches and Emerging Trends, 2026)
This research addresses an existing deficiency in the field of Austronesian micro-dialectology by exploring the structural differences between the closely situated Kaili Ledo and Kaili Ado dialects found in Central Sulawesi. The objective was to compare 50 adjectives, with primary data gathered from native speakers in Palu and Sigi through observational (simak) and conversational (cakap) approaches, which were subsequently examined using intralingual pairing. The results effectively respond to the research inquiries: both dialects possess a common grammatical foundation wherein adjectives operate as stative verbs through mandatory prefixation (na-/ma-), while also exhibiting consistent micro-dialectal variation. From a phonological standpoint, an observable vowel transformation from /a, i/ to /o/ along with the addition of glottals appears in Ado (na ka vs. na’ko), in addition to final nasal prolongations (nalanga vs. nalangan). On a lexical level, complete root substitutions differentiate behavioral ideas (jilere vs. nyenye). In terms of structure, asymmetries are most evident in less desirable contexts, as Ledo utilizes a bound root (na ’da), whereas Ado opts for a phrase (ado nabelo). In summary, this structural alignment facilitates the creation of a cohesive local education program.